Is Public Debt Reduction Worthwhile? - Bev Dahlby (The School of Public Policy Publications)
This paper examines whether reducing Canada’s federal debt is a worthwhile policy objective, in light of economists’ advice and public opinion favouring debt reduction. As well, the federal government has projected a gradual decrease in its debt-to-GDP ratio over the next 30 years. Reducing the public debt means that governments have to adopt a policy of fiscal austerity. This paper focuses on the trade-offs of fiscal austerity — short-term sacrifices for long-term benefits.